What does family building mean? A qualitative exploration and a new definition: a UK-based study - Bola Grace; Jill Shawe; Geraldine Barrett; Nafisat Ohunene Usman; Judith Stephenson (BMC, 2022)
Plain language summary Global health policies have emphasised the importance of improving individual's knowledge of sexual and reproductive health. Fertility awareness literature highlights a disproportionately higher number of articles related to pregnancy-prevention compared to pregnancy-planning, which is justifiable in many contexts. However, the recent concerted effort to improve fertility awareness warrants a closer investigation of basic terminologies in the field. For example, although the term family planning encompasses attaining the desired number of children and spacing pregnancies, it is almost synonymous with not having children, while there is currently no widely accepted equivalent terminology for planning to have children, either in general usage or clinical settings. We conducted 35 qualitative in-depth interviews on men, women and healthcare professionals who were sampled from a UK cross-sectional survey. When asked what 'family planning' meant to them, study participants stated avoidance of pregnancy. They viewed it as an "umbrella term for the use of contraception methods", that "paradoxically, the term family planning almost has a negative connotation regarding having a family," but could not state similar terminology for planning a family. We introduced family building and provided a new definition. We believe that some balance in the global public health messages, including revisiting widely used terminologies can help bridge the gap in reproductive health literature, and contribute to the effort to improve fertility knowledge. Additionally, this has implications for promotion of preconception and optimising reproductive health in relevant policies, processes and practices, in order to help people achieve their desired fertility intentions, whatever they may be.